A New Twist on Studying the Development of Dynamic Spatial Transformations: Mental Paper Folding in Young Children. Issue 1 (24th February 2013) - Harris, Justin; Newcombe, Nora S.; Hirsh‐Pasek, Kathy
ABSTRACT The relation of spatial skills to academic success in areas such as math and science has sparked discussion in early education around how spatial thinking skills might be included in early schooling. Planning and evaluating new curricula or interventions requires understanding these skills and having the means to assess them. Prior developmental research focused primarily on one aspect of dynamic spatial transformations (DST), namely mental rotation. This study broadens our knowledge by addressing another important DST, namely mental folding. We devised a new test suitable for young children. Performance of 180 children between 4 and 7 years suggests that mental folding appears at around 5.5 years of age, although there were also marked individual differences. These data on the emergence of DST suggest that educational programs targeting this skill could start in preschool or kindergarten and provide a means to assess the effectiveness of such efforts.